2015
DOI: 10.1136/annrheumdis-2013-205138
|View full text |Cite
|
Sign up to set email alerts
|

CD226 (DNAM-1) is associated with susceptibility to juvenile idiopathic arthritis

Abstract: The CD226 gene has been identified as novel association with JIA, and a SNP near CD28 as a suggestive association. Both genes are probable candidate risk factors, since they are involved in costimulation of T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…21 A genetic association study was also performed in patients from Northwest European descent and confirmed the association of several genes (PTPN22, VTCN1, the IL2-IL21 region, ANKRD55 and TNFA) with JIA. 19 We confirmed the JIA-U susceptibility locus in rs11074967, which is located near the PRM1 gene. PRM1 is a member of protamines which have been isolated from spermatozoa, playing a role in sperm chromatin condensation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…21 A genetic association study was also performed in patients from Northwest European descent and confirmed the association of several genes (PTPN22, VTCN1, the IL2-IL21 region, ANKRD55 and TNFA) with JIA. 19 We confirmed the JIA-U susceptibility locus in rs11074967, which is located near the PRM1 gene. PRM1 is a member of protamines which have been isolated from spermatozoa, playing a role in sperm chromatin condensation.…”
Section: Discussionsupporting
confidence: 68%
“…The r 2 value for linkage disequilibrium had to be less than 0.8 between adjacent loci and the minor allele frequency had to be larger than 0.05 in the CHB. Based on the above criteria, we finally included 84 SNPs in or near 60 loci: ANTXR2, 18 CXCR4, 18 CD226, 19 TNFA, 19 MIF, 19 CD28, 19 KIAA1109, 19 PSMC6, 20 PSMA3, 20 STAT4, 21 24 IL20, 24 CDGAP/ARHGAP31, 25 C3orf1/ TIMMDC1, 25 IL15, 25 NRBF2-EGR2, 25 JMJD1C, 25 REEP3, 25 IGF1R-FAM169B, 25 CHD9-TOX3, 25 IRF5, 26 BLK, 27 C5orf30, 27 CD247, 27 ORMDL3, 27 PTPRC, 27 ERAP1, 28 LPP, 29 TRAF1/C5, 30 IL2RA, 31 Intergenic, 31 32 The selected SNPs were genotyped by MassARRAY platform (Sequenom, San Diego, California, USA) and iPLEX Gold Genotyping Assay, and analysed by TYPER software V.4.0. The PCR was performed with the GeneAmp PCR System 9700 thermocycler (ABI, Foster City, California, USA).…”
Section: Single Nucleotide Polymorphism Choicementioning
confidence: 99%
“…It is expressed on T and NK cells and is involved in co-stimulation of these cells. This association was not seen on a follow-up Immunochip study but the association was confirmed in a meta-analysis [59]. Other polymorphisms associated with JIA are located in the IL2-IL21 region, the AFF3 gene and ANKRD55 [45,59,60].…”
Section: Genetics Of Oligoarticular Jia/polyarticular Rf-negative Jiamentioning
confidence: 99%
“…In a 2014 study Reinards et al performed a genetic association study which identified a polymorphism in the CD226 ( DNAM1 ) gene in association with JIA [59]. DNAX accessory molecule-1 is a type 1 membrane protein belonging to the Ig-supergene family.…”
Section: Genetics Of Oligoarticular Jia/polyarticular Rf-negative Jiamentioning
confidence: 99%
“…TIGIT competes with the costimulatory molecule CD226 for binding to the poliovirus receptor (PVR)/Nectin-like-5/CD155 prominently expressed on APCs (17). CD226 has been identified as an autoimmune susceptibility gene, with a SNP (Gly307Ser; rs763361) linked to type 1 diabetes (T1D), multiple sclerosis (MS), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) Wegners granulomatosis, celiac disease (CD), and juvenile idiopathic arthritis (JIA)(18, 19). This recently described axis shares many parallel functions with the CD28:CTLA-4 pathway in terms of promoting or inhibiting T cell activation, respectively (2022).…”
Section: Introductionmentioning
confidence: 99%